Emotional intelligence characterization in university students at a nutrition bachelor’s degree - Torres-Zapata , Ángel Esteban; Lara-Gamboa , Carmen Cecilia; Pérez-Jaimes , Alejandra Karina; Estrada-Reyes , César Uziel; Brito Cruz, Teresa del Jesús (Horizonte Sanitario, 2022)
Objective: Identify the levels of emotional intelligence possessed by students of a Bachelor of Nutrition degree at a university in southeastern Mexico. Materials and methods: According to reviewed documental sources this is a quantitative study, with a descriptive non-experimental approach. In this research, a validated Salovery and Meyer TMMS-24, adapted to Spanish, was applied; this instrument consists of 24 items, subdivided into three subscales or dimensions of the Likert type made up of five items. The sampling was nonprobabilistic, including 172 university students, who accepted the terms of the informed consent. For data analysis, the SPSS v.25 program was executed to assembly the information obtained through descriptive statistics (frequency, mean, median and percentage) and variability measures (range, standard deviation and variance). A t-Student test was performed for the analysis of means according to the levels, with a p value <0.005 to determine statistically significant differences. Results: 52.91% of the students are located at a level of “adequate attention”, but 47.1% must improve. In relation to the level of understanding, 43.60% have adequate clarity in this sphere of emotional intelligence, while 56.60% must improve this component and 52.33% have adequate regulation, while 47.67% must improve. No statistically significant differences were found; as well as there were no differences in the means between both genders (p = ≥0.05). Conclusions: The study population showed an adequate management level of their emotional intelligence, being emotional perception the one that is presented more frequently as adequate, however, the clarity of feelings presents the lowest levels, so It is evident the need to carry out intervention programs in university students to promote further development of the dimensions that make up emotional intelligence. Keywords: Emotional intelligence; Students; Nutrition; University.